RETRACTED: MicroRNA‐425‐3p inhibits myocardial inflammation and cardiomyocyte apoptosis in mice with viral myocarditis through targeting TGF‐β1 - Junhua Li; Jiehong Tu; Hong Gao; Lu Tang (Immunity, Inflammation and Disease)
Abstract Objective Emerging articles have profiled the relations between microRNAs and viral myocarditis. This research was unearthed to explore the capacity of miR‐425‐3p on cardiomyocyte apoptosis in mice with viral myocarditis and its mechanism. Methods A total of 120 mice were classified into 4 groups in a random fashion (n = 30). The mice were intraperitoneally injected with coxsackievirus type B3 (CVB3) to induce myocarditis. On the 7th day after CVB3 infection, 10 mice in each group were euthanized to assess the heart function indices of mice, observe the pathological conditions, detect myocardial tissue apoptosis, and measure the inflammatory factor levels in myocardial tissues. Expression of miR‐425‐3p, transforming growth factor (TGF‐β1), and apoptosis‐associated proteins in myocardial tissues was determined. The remaining 20 mice in each group were used for survival observation. The luciferase activity assay was implemented to validate the relationship between miR‐425‐3p and TGF‐β1. miR‐425‐3p mimic was transfected into mouse cardiomyocytes HL‐1 and then infected with CVB3 to further verify the regulatory effect of miR‐425‐3p on the cardiomyocyte apoptosis in viral myocarditis. Results miR‐425‐3p was lowly expressed in myocardial tissues of mice with viral myocarditis. Overexpressed miR‐425‐3p improved the cardiac function, alleviated pathological conditions, reduced cardiomyocyte apoptosis, decreased Bax and cleaved Caspase‐3 expression, elevated Bcl‐2 expression, decreased levels of inflammatory factors and improved survival rate of mice with viral myocarditis. Luciferase activity assay verified that miR‐425‐3p could bind to TGF‐β1, and overexpressed miR‐425‐3p suppressed TGF‐β1, p‐smad2/smad2 and p‐smad3/smad3 expression. In vitro experiments further verified that overexpression of miR‐425‐3p inhibited the apoptosis of CVB3‐HL‐1 cells, and the addition of TGF‐β1 would reverse this effect. Conclusion Our research indicates that miR‐425‐3p is poorly expressed in myocardial tissues of mice with viral myocarditis. Overexpressed miR‐425‐3p inhibits cardiomyocyte apoptosis and myocardial inflammation in mice with viral myocarditis as well as improves their survival rates through suppressing the TGF‐β1/smad axis.